Pengaruh Work-Life Balance Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Mediasi Kepuasan Kerja Pada Kantor - Tasriani, Tasriani; Khairunnisa, Silvi; Septianingsih, Rika (Akuntansi & Ekonomika, 2026)
This study aims to examine the effect of work-life balance and work environment on employee performance at the Office of the Ministry of Religious Affairs of Pekanbaru City, with job satisfaction as an intervening variable. This study employs a quantitative method using SEM-PLS analysis through SmartPLS 4. Data were collected through questionnaires distributed to 57 respondents using the census method. The results show that work-life balance does not have a significant effect on either job satisfaction or employee performance, while the work environment has a significant effect on both job satisfaction and employee performance. Job satisfaction also has a significant effect on employee performance and is able to mediate the effect of the work environment on employee performance, but it is unable to mediate the effect of work-life balance on employee performance.